A2-Astrocyte Activation by Short-Term Hypoxia Rescues α-Synuclein Pre-Formed-Fibril-Induced Neuronal Cell Death - Ha Nyeoung Choi; Seon-Hee Kim; Min Gi Jo; Bina Lee; Young Jin Kim; So Eun Lee; Jeong Hyun Lee; Hye Min Seong; Seong Jae Kim; Sang Won Park; Hye Jung Kim; Heeyoung Kang; et al. (Biomedicines)
Background/Objectives: Parkinson’s disease (PD) is a neuro-degenerative disease for which a radical cure is not available, only symptomatic control. Studies have shown that hypoxia may have disease-modifying effects on PD. Methods: Herein, we investigated whether short-term hypoxia activates astrocytes and whether it has a protective effect on pre-formed fibril (PFF)-treated primary cortical neurons. Results: Long-term hypoxia suppresses astrocyte activation and induces cell death, whereas short-term hypoxia activates astrocytes without affecting cellular apoptosis or viability. Short-term hypoxia restored the cellular apoptosis and viability of PFF-treated neurons and reduced toxic phospho-α-synuclein (p-α-syn) aggregation. Similarly, the short-term hypoxia-exposed astrocyte-conditioned medium rescued cellular apoptosis and the viability of PFF-treated neurons and p-α-syn expression. Quantitative polymerase chain reaction revealed that short-term hypoxia promotes protective A2 astrocytes and suppresses toxic A1 astrocytes. Conclusions: Our findings suggest that short-term hypoxia has a neuro-protective effect against PD by activating protective A2 astrocytes, which rescue PFF-induced neuronal cell death. This provides insights into the clinical implications of short-term hypoxia as a disease-modifying PD strategy.